Response Surface Methodology for the Optimization of Alpha Amylase Production by Serratia marcescens SB08 (Biological Sciences - PJSIR, 2008)
In this work, central composite design combining with response surface methodology was successfully employed to optimize medium composition for the production of alpha amylase by Serratia marcescens SB08 in submerged fermentation. The process parameters that influence the enzyme production were identified using Plackett- Burman design. Among the various factors screened, inoculum concentration, pH, NaCl and CaCl2 were found to be most significant. The optimum level of pH was 5.0, inoculum concentration 3%, NaCl 0.30 g/l and CaCl2 0.13 g/l. The actual enzyme yield before and after optimization was 56.43 U/ml and 87.23 U/ml, respectively. Thus, it is advisable to the microbial industry sponsors to apply such profitable bioprocess to maintain high yield for mass production of a amylase.